การพัฒนากรอบมาตรฐานคุณวุฒิของประเทศไทย สำหรับวิชาชีพสารสนเทศ - ปทุมพงษ์, นุจรินทร์ (บรรณศาสตร์ มศว, 2016)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อสังเคราะห์หลักสูตรระดับปริญญาตรีที่เกี่ยวข้องกับวิชาชีพสารสนเทศ และศึกษาความต้องการหลักสูตรและสมรรถนะสำหรับบัณฑิตระดับปริญญาตรีในวิชาชีพสารสนเทศของผู้มีส่วนได้ส่วนเสียในประเทศไทยเพื่อนำมาพัฒนากรอบมาตรฐานคุณวุฒิสำหรับวิชาชีพสารสนเทศของประเทศไทย วิธีการดำเนินการวิจัยใช้การวิจัยแบบผสมโดยวิธีวิจัยเชิงคุณภาพ ได้แก่ การสังเคราะห์วรรณกรรม การสังเคราะห์หลักสูตร การสัมภาษณ์เชิงลึก และการประชุมสนทนากลุ่ม และใช้วิธีวิจัยเชิงปริมาณในการศึกษาความต้องการหลักสูตรและสมรรถนะสำหรับบัณฑิตระดับปริญญาตรี ประชากรและกลุ่มตัวอย่างที่ใช้ในการวิจัยเชิงปริมาณ ได้แก่ อาจารย์ผู้สอนในหลักสูตรที่เกี่ยวข้องกับวิชาชีพสารสนเทศในประเทศไทย จำนวน 232 คน ผู้มีส่วนได้ส่วนเสียคือ ห้องสมุดสถาบันอุดมศึกษา จำนวน 118 แห่ง และองค์กรธุรกิจเอกชน จำนวน 400 แห่ง กลุ่มผู้ให้ข้อมูลหลักสำหรับการวิจัยเชิงคุณภาพ ได้แก่ อาจารย์ผู้สอนในหลักสูตรที่เกี่ยวข้องวิชาชีพสารสนเทศ จำนวน 8 คน ผลการวิจัยพบว่า 1) หลักสูตรระดับปริญญาตรีที่เกี่ยวข้องกับวิชาชีพสารสนเทศประกอบด้วยรายวิชาพร้อมสมรรถนะของการเรียนแต่ละรายวิชา จำนวน 73 รายวิชา 2) ผู้มีส่วนได้ส่วนเสียในหลักสูตรที่เกี่ยวข้องกับวิชาชีพสารสนเทศมีความต้องการรายวิชาบังคับร่วมกันของทั้งสามกลุ่มสาขาวิชา จำนวน 11 วิชา และมีความต้องการสมรรถนะของนักวิชาชีพสารสนเทศ 3 ด้าน คือ สมรรถนะด้านความรู้ 30 เรื่อง ด้านทักษะ 13 ทักษะ และด้านคุณลักษณะส่วนบุคคล 7 คุณลักษณะ และ 3) กรอบมาตรฐานคุณวุฒิสำหรับวิชาชีพสารสนเทศของประเทศไทย ประกอบไปด้วย ชื่อสาขา ระดับการศึกษา ขอบเขตเนื้อหา สมรรถนะของบัณฑิต โครงสร้างหลักสูตร และเนื้อหาสาระสำคัญของหมวดวิชาเฉพาะในหลักสูตร Abstract This research aims to synthesize the Bachelor Degree curriculum for the Information Profession. In addition, it seeks to investigate the needs of the curricula and the performance of Bachelor Degree Graduates in the Information profession. The information will be gathered from the stakeholders in Thailand in order to develop the Thai Qualification Framework for Thailand Information Profession. Quantitative and qualitative methodologies have been embraced in the current study. The qualitative methods applied in this research were carried out by using a synthesis of the literature and the curriculum, as well as by conducting in-depth interviews and focus groups. Quantitative methods were utilized to study the needs of the curricula and the performance of Bachelor Degree Graduates in the Information profession. The population and sample groups in quantitative method consisted of 232 teachers who were teaching courses related to Information profession in Thailand. The stakeholders consisted of 118 university libraries and 400 private business organizations. With respect to the qualitative method, the key informants were 8 teachers who teach in courses related to the Information profession. The results revealed the following information: 1) The Bachelor Degree Program in Information Profession consists of 73 courses including the performance of each course. 2) The stakeholders, who were involved in the Information Profession Program, preferred to share the 11 co-requisite courses among three programs. According to performance, three aspects of the Information profession’s performance were the demands of the stakeholders. In terms of knowledge competency, 30 additional subjects relating to the information profession were needed. Moreover, competency, involving 13 skills and 7 personal characteristics, were also required by stakeholders. 3) Suggestions were given, relating to the Thai Qualification Framework for the Information Profession, which consisted of the name of the program, the educational level, the performance of graduates, the curriculum structure, and the important content of the core courses in the curriculum. All of these have also been retrieved in the current study. คำสำคัญ กรอบมาตรฐานคุณวุฒิ, วิชาชีพสารสนเทศ Keywords Qualification framework, Information profession